Current approaches to the use of antiplatelet and anticoagulant drugs in pregnant women with thrombocytopenia caused by hemostasis activation - O. L. Mysik; M. S. Zainulina (Акушерство, гинекология и репродукция, 2021)
Introduction. At present, hemostasis disorders still hold one of the lead places in the pathogenesis of reproductive losses associated with high risk of miscarriage and remain one of the major causes for developing serious obstetric complications. Relevance, efficacy and safety of using drugs containing acetylsalicylic acid (ASA) and low molecular weight heparins (LMWH) in pregnant women with thrombocytopenia comorbid with intravascular coagulation activation remain pressing issues. The study of thrombocytopenia pathogenesis during pregnancy and search for new methods of hemostasis correction are accounted for by high risk of developing diverse perinatal complications and necessity to conduct prophylactic measures for their prevention.Aim: to study hemostasis changes and clinical outcomes in pregnant women with thrombocytopenia, to substantiate the use of antiplatelet agents and anticoagulants in pregnant women with activated intravascular blood coagulation for preventing development of thromboembolic and placenta-associated complications of pregnancy.Materials and Methods. A multicenter prospective study was conducted by enrolling 299 pregnant women at a gestational age of22.85 [22.00; 25.00] weeks, whose average age was 31.06 [27.75; 35.00] years. There were distinguished three groups: main group (n = 124) consisted of pregnant women with lowered platelet count and activated intravascular blood coagulation, who received ASA preparations and LMWH in prophylactic doses for 4 weeks; pregnant comparison groups (n = 125) received no such drugs; control group (n = 50) consisted of women with normal platelet counts during physiological pregnancy. All patients underwent clinical, anamnestic and laboratory examination, and the clinical outcomes of pregnancy were assessed.Results. It was found that use of ASA (a combined drug: ASA 75 mg + magnesium hydroxide 15.2 mg/day) and LMWH (enoxaparin sodium) in pregnant women from the main group were noted to improve hemostasis parameters: via markedly increased platelet count, decreased fibrinogen level, prothrombin index as well as normalized antithrombin III level (p < 0.01). It was also found during treatment that the D-dimer level and the rate (83.6 ± 2.3 % and 72.4 ± 2.7 %) and the degree (86.4 ± 2.7 % and 74.4 ±2.8 %) of platelet aggregation in the main group (in contrast with comparison group) were significantly decreased (p < 0.01). The frequency of detected chronic placental insufficiency was significantly higher (p < 0.01) in the comparison group (n = 50; 41.32 %) vs. the main group after receiving ASA and LMWH (n = 20; 16.52 %). The incidence of moderate (p = 0.016) and severe (p = 0.018) preeclampsia was significantly higher in the comparison group vs. the main group. While comparing the volume of blood loss during delivery, there were no differences between the main group and the comparison group (p = 0.46); it was noted only a statistically significant difference compared to the control group (p = 0.04), in which the lowest blood loss was found (337.9 [200.0; 600.0] ml) in comparison with the other two groups (p1,3 = 0.05; p2,3 = 0.04). It should be noted that the volume of blood loss in all groups remained within the physiological permissible range.Conclusion. Our clinical and laboratory study allowed to substantiate relevance of using ASA and LMWH drugs in pregnant women with thrombocytopenia comorbid with confirmed activation of intravascular blood coagulation, for prevention of thromboembolic and placenta-associated complications of pregnancy as well as proved safety of such drugs during pregnancy.